(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Total Quality Management increase in productivity, its reliability and decrease in cost of the product. It is an effort to be put in by every work organization, so as to achieve performance improvement. It is a strategic objective targeting its permeation in every aspect. Continuous efforts among all the personnel at every level necessary for continuous improvement and customer satisfaction.